The impact of digital transformation on public sector organizational commitment: A case study of public management practices - Engkus, Engkus (Edelweiss Applied Science and Technology, 2025)
Digital transformation in the public sector significantly reshapes organizational structures, service delivery, and employee engagement. This study aims to examine the critical factors influencing digital transformation in public sector institutions, focusing on leadership, employee commitment, resistance to change, and technological adaptation. Using a systematic literature review approach, the research identifies key success factors, including strong leadership, comprehensive training, cross-departmental collaboration, and robust technological infrastructure. The findings indicate that successful digital transformation enhances efficiency, responsiveness, and employee commitment, particularly when supported by clear communication and adequate training. However, resistance to change remains a challenge, especially when employees perceive automation as a threat to job security. Leadership plays a crucial role in addressing these concerns and fostering a culture of innovation and inclusivity. Furthermore, integrating advanced technologies such as AI, IoT, and big data analytics can significantly improve public service delivery but must align with organizational objectives to maintain public trust. The study concludes that a balanced approach—considering both technological advancements and human factors—is essential for sustainable digital transformation. These insights provide practical implications for policymakers and public sector leaders in navigating digital transformation while ensuring organizational performance and public confidence.